Isolation of terpenoid compound of n-hexane extract of Marsilea crenata Presl.. - Ma'arif, Burhan; Agil, Mangestuti; Widyowati, Retno (University of Muhammadiyah Malang, 2019)
Isolation, identification, and structure elucidation of terpenoid compounds from an n-hexane extract of Marsilea crenata Presl., had been done. The leaves of M. crenata was extracted using n-hexane solvent. The extract then separated with vacuum column chromatography and open column chromatography to obtain the isolate. Furthermore, the isolate was identified and elucidated using UV-Vis, FT-IR, 1H-NMR, 13C- NMR, and 2D-NMR (COSY, HMQC, and HMBC). The identification and elucidation of the isolated structure from an n-hexane extract of M. crenata leaves indicate the isolate was a pentacyclic triterpenoid.